DEVELOPMENT OF STUDENT WORKSHEETS INTEGRATED WITH PBL-STEM ON TEMPERATURE AND HEAT MATERIAL - Rochman, Syaiful; Algiranto, Algiranto; Ekasari, Aprilita; Turaqulov, Botir T (EduFisika: Jurnal Pendidikan Fisika, 2024)
The purpose of this study is to create a Problem Based Learning approach integrated with Science, Technology, Engineering, and Mathematics (STEM), especially in the field of Physics. The goal is to improve students' creative thinking skills in learning about temperature and heat. The resulting Student Worksheets will be designed to be valid, practical, and effective. This study involves research and development activities using a 4-D model consisting of the stages of definition, design, development, and dissemination. This research was conducted at SMP Muhammadiyah Kartosentanan in the 2023/2024 academic year. Data collection was carried out through the use of validation sheets, student questionnaires, and test devices. Furthermore, data was collected using the N-Gain formula. PBL-STEM-based student worksheets were considered valid by the media validator with an agreement of 96%, the material validator 89%, and the instrument validator 95%. The feasibility analysis shows that the PBL-STEM-based student worksheets produced are very practical for students to use, as evidenced by the N-Gain results of 0.92 with a high category. This study concludes that the student worksheets developed based on PBL-STEM are valid, practical, and useful in improving students' creative thinking skills